Trends and Innovations in Education of Nigerian Nomadic Population (Foro de Educacion, 2016)
Nigerian population is characterised with multiplicity of ethnic and linguistic groups. These groups in their various geographical and climatic configurations are occupationally distinctive. The northern arid region rears cattle and fishing is predominant in the riverine and coastal south of the country. The search for grazing their animals have made the Fulani cattle rearers a mobile population, so also the fisherfolk, farmers, hunters and gatherers are not stationary because of continuous search for livelihood. Upon this culture of mobility, education of their children who move with them suffers. However, the government social responsibility has been made manifest in the provision of modified education for these groups of underserved Nigerians to meet their needs. Nomadic education is arranged for them and how far has nomadic education fared and the receivers fortunes, innovations to reposition the education programme of the nomads and the strategies for improvement are all discussed in this paper; using historical research method. Ultimately, the paper concluded bemoaning series of policies that are formulated and programmes mounted in the country, but which their implementation and monitoring are lukewarm. Therefore, demonstration of genuine commitment and disposition to policy formulation and implementation are advocated.